ANALISIS PERBANDINGAN KINERJA KEUANGAN PT. MULTIBINTANG INDONESIA SEBELUM DAN SESUDAH DIAKUISISI OLEH HEINEKEN INTERNATIONAL BV - Putra, I Kadek Adi; Badjra, Ida Bagus (E-Jurnal Manajemen; Vol 7 No 10 (2018)DO - 10.24843/EJMUNUD.2018.v07.i10.p09, 2018)
Among the business strategies utilized by companies to increase their business growth and financial performance is external expansion through acquisition. The aim of this research is to analyze the difference in the financial performance of PT. Multi Bintang Indonesia Tbk before and after being acquired. The evaluation of financial performance is conducted by using the liquidity ratios (current ratio and quick ratio), solvability ratios (debt to asset ratio and debt to equity ratio), activity ratios (fixed assets turnover and total assets turn over) and the profitability ratio (net profit margin, return on investment and return on equity). The data used are attained from the annual financial statement of PT. Multi Bintang Indonesia Tbk before acquisition, in the periods of 2010-2012, and after the acquisition, in the periods of 2014-2016. The analysis technique utilized is the Wilcoxon signed rank test. Based on the data analysis results, all the financial ratios used to measure the financial performance show that there were no significant differences in the performance of PT. Multi Bintang Indonesia Tbk before and after the acquisition. Keywords: financial performance, acquisition, PT. Multi Bintang Indonesia Tbk